Justice A Legal Analysis of Medical Marijuana Regulation - Bambang Sugeng Rukmono; Sandi Yudha Prayoga (Contrarius, 2025)
Indonesia currently prohibits marijuana under its classification as a Category I narcotic, which disallows any form of medical use. However, various studies have shown that marijuana can potentially treat up to 36 different diseases. This research aims to analyze the appropriate regulatory model for medical marijuana based on the principle of justice as rooted in Pancasila. The study adopts a normative legal research method, relying on secondary data comprising primary, secondary, and tertiary legal materials. The findings reveal three key points. First, current legal provisions in Indonesia do not specifically regulate the use of marijuana for medical purposes, and existing regulations address narcotics only in general terms. Second, global research, including positions taken by the World Health Organization and the United Nations, supports the medical benefits of marijuana, yet the Indonesian government maintains a restrictive stance. Third, legalizing medical marijuana could be achieved through revising the Narcotics Law and removing marijuana from the list of Category I narcotics. In conclusion, the development of a regulatory model for medical marijuana based on Pancasila justice requires balancing scientific evidence, legal reform, and ethical considerations in public health policy.